The first-party professional certification body: hope and reality - I Gede Darmawijaya (Program Studi Manajemen Divisi Kamar, 2022)
The first-party professional certification body in higher educational institutions plays a significant role in filtering the quality of the graduates as it certifies the students' competency. The low quality of the assessment process and the negative perceptions of the graduates indicated the mismanagement of this body that motivated the researcher to investigate the understanding of this body’s stakeholders toward the qualification scheme of competency. The objectives of this research were to identify the needs of five stakeholders and their understanding of the qualification scheme. This research made use of the deep interview to collect data from purposively listed informants. The analysis method applied for this research was Stakeholder Analysis and Interpretative Phenomenological Analysis (IPA). The results showed that the needs of stakeholders were not identified, so they were not addressed in designing the business process and its cascading assessment instruments. The second finding was that the understanding of the stakeholders toward the qualification scheme was very low, affecting their low performance in conducting competency assessments. The implications of the findings are the advisory and management teams need to identify the needs of stakeholders. Furthermore, dissemination or training or workshop on designing qualification schemes and their cascading instruments are urgently needed.